Essential oil of three air-dried parts of Etlingera brevilabrum - Behnam Mahdavi; W. A. Yaacob; Laily B. Din; Siti Aishah Mohd Ali (Taylor & Francis Group, 2013)
Essential oil from the air-dried rhizomes, stems and leaves of Etlingera brevilabrum were hydrodistilled using a Clevenger-type apparatus and identified by GC and GC-MS. Monoterpene hydrocarbons dominated the oils from the stems and leaves (66.8 and 89.8 % respectively) whereas oxygenated monoterpenes were dominant in the rhizomes (40.2 %). Eucalyptol (27.6 %), β-pinene (13.4 %), caryophyllene oxide (10.5 %) and α-thujene (10.1 %) were the major compounds in the rhizomes oil; limonene (28.6 %), β-pinene (21.6 %), α-thujene (13.9 %) and caryophyllene oxide (4.6 %) in the stems; and β-pinene (52.6 %), α-thujene (28.6 %) and o-cymene (7.8 %) in the leaves.